2019
DOI: 10.1002/hbm.24784
|View full text |Cite
|
Sign up to set email alerts
|

Neural oscillations and connectivity characterizing the state of tonic experimental pain in humans

Abstract: Pain is a complex phenomenon that is served by neural oscillations and connectivity involving different brain areas and frequencies. Here, we aimed to systematically and comprehensively assess the pattern of neural oscillations and connectivity characterizing the state of tonic experimental pain in humans. To this end, we applied 10‐min heat pain stimuli consecutively to the right and left hand of 39 healthy participants and recorded electroencephalography. We systematically analyzed global and local measures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 78 publications
4
37
0
Order By: Relevance
“…Our study builds on previous findings that identified pain‐evoked oscillatory activity in healthy individuals within a specific functional band (Furman et al, 2017; Huishi Zhang, Sohrabpour, Lu, & He, 2016; May et al, 2019; Nickel et al, 2019; Nir, Sinai, Moont, Harari, & Yarnitsky, 2012; Ploner et al, 2006; Schulz et al, 2015). These previous studies mostly relied on electroencephalography (EEG) and so the findings had limited spatial resolution.…”
Section: Discussionsupporting
confidence: 76%
“…Our study builds on previous findings that identified pain‐evoked oscillatory activity in healthy individuals within a specific functional band (Furman et al, 2017; Huishi Zhang, Sohrabpour, Lu, & He, 2016; May et al, 2019; Nickel et al, 2019; Nir, Sinai, Moont, Harari, & Yarnitsky, 2012; Ploner et al, 2006; Schulz et al, 2015). These previous studies mostly relied on electroencephalography (EEG) and so the findings had limited spatial resolution.…”
Section: Discussionsupporting
confidence: 76%
“…Based on these data, the authors have proposed a predictive coding model including a bottom-up (gamma) and top-down (beta) component ( Song et al, 2019 ). Finally, in humans, a recent EEG study showed that the sensorimotor cortex is more strongly connected to the medial prefrontal cortex at alpha frequencies during tonic pain, suggesting alpha band activity in tonic pain to be associated with bottom-up instead of top-down signaling ( Nickel et al, 2020 ). Nevertheless, the focus of these studies was on generic interactions (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…As predicted, skin vibration employing multiple frequencies had a unique and significant impact on both pain perception (Table 1) and pain tolerance (Table 2) when compared to no skin vibration (baseline), which was not the case for either VA or SP. Given that pain is a complex phenomenon promoted by a network of neurons (48) generating neural oscillations in different brain areas and frequencies (49), one possible explanation for the significant results in MVA when compared to baseline and SP is that the differences between frequencies generate beats, which might increase the effect of entrainment of the oscillatory activity in the brain rhythms (50).…”
Section: Discussionmentioning
confidence: 99%